Platelet-rich plasma: updating of extraction devices - Raquel Moreno; Marisa Gaspar Carreño; Jose María Alonso Herreros; Jose Antonio Romero Garrido; Piedad López-Sánchez (Farmacia Hospitalaria)
Propose: To describe PRP extraction devices, through a review of kits available in Spain, taking into account AEMPS and SEFH working groups (GPS, Farmacotecnia, Hemoderivados groups) contributions. Methods: Three independent searches about PRP extraction devices were carried out. Device suppliers were contacted and an individually meeting was called with each one. Characteristics of each device was reviewed by virtual demonstration. A kits comparison chart was made with all the information acquired. Kits were classified as Closed-Technique and Opened- Technique in accordance with the AEMPS technical committee report. Results: Ten devices were found: ACP®; Angel®, Cascade®, Endoret ®, GPS®, Magellan®, Minos®, Ortho-pras®, Smart-prepr® and Tricell®. However, we could found out the mechanism in detail of seven of them. Information about Cascade®, Magellan ® and Smart-prepr® kits was not enough. Conclusion: The review provided the main PRP extraction devices available with CE marking and its distinguishing characteristics, however, it is crucial to pay attention to PRP extraction procedure and administration, to guarantee the final product quality. Pharmacy Department must get involved in the device selections due to the close link with the manufactured drug quality. Working together with the AEMPS will contribute to defining extraction procedure specifically.